2014
DOI: 10.1371/journal.pone.0105040
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprint of Telemedicine Solutions - Unexplored Opportunity for Reducing Carbon Emissions in the Health Sector

Abstract: BackgroundThe healthcare sector is a significant contributor to global carbon emissions, in part due to extensive travelling by patients and health workers.ObjectivesTo evaluate the potential of telemedicine services based on videoconferencing technology to reduce travelling and thus carbon emissions in the healthcare sector.MethodsA life cycle inventory was performed to evaluate the carbon reduction potential of telemedicine activities beyond a reduction in travel related emissions. The study included two reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(136 citation statements)
references
References 29 publications
5
128
0
3
Order By: Relevance
“…Another leverage point to reduce the health care system's carbon footprint lies in avoiding unnecessary or even harmful treatments and medical interventions or misallocation of patients [10]. For example, avoiding intensive care in hospitals [42] or providing telemedicine solutions can reduce costly and resourceintensive forms of care and at the same time improve health outcomes and quality of life, particularly for people with chronic conditions [43]. Finally, a systemic shift from curative to preventive and from hospital to ambulatory care would likely reduce the health carbon footprint [1].…”
Section: Discussionmentioning
confidence: 99%
“…Another leverage point to reduce the health care system's carbon footprint lies in avoiding unnecessary or even harmful treatments and medical interventions or misallocation of patients [10]. For example, avoiding intensive care in hospitals [42] or providing telemedicine solutions can reduce costly and resourceintensive forms of care and at the same time improve health outcomes and quality of life, particularly for people with chronic conditions [43]. Finally, a systemic shift from curative to preventive and from hospital to ambulatory care would likely reduce the health carbon footprint [1].…”
Section: Discussionmentioning
confidence: 99%
“…A more interesting finding was reported by Holmner et al who showed that by replacing a physical meeting with telemedicine, carbon reduction can be achieved, thus offering a greener choice than conventional meeting 5. As shown in the decade-long result, endoscopy-related teleconferences are gaining popularity 2.…”
Section: Discussionmentioning
confidence: 92%
“…11 The rehabilitation department at the University of Sweden, showed that replacing face-to-face consultation with telemedicine reduced carbon dioxide emission 40 to70 times less. 12 In conclusion, all countries (especially developing countries which are more vulnerable to climate change) can benefit from the environmental advantages of telemedicine which help reduce the destructive effects of global warming. Therefore, healthcare centers should be informed about the benefits of telemedicine to encourage the implementation and development of this technology.…”
Section: Dear Editormentioning
confidence: 99%